Intralobar pulmonary sequestration: An intraoperative finding - Acuña Fernández, Leoncio (2016)
The case of a 3 year-old female patient, who was intraoperative diagnosed with intralobar pulmonary sequestration located in the lower lobe of the left lung, is reported. Pulmonary sequestration is a rarecongenital pulmonary malformation characterized by a non-functional mass of lung tissue, which is irrigatedby an abnormal systemic artery, generally originated in the descending aorta; its intralobar variety manifests as recurrent pneumonia. Definitive diagnosis is made after identifying the abnormal artery with imaging techniques (MSCT with contrast and Doppler echocardiography). There is no national incidence study on this condition. The following case is the first pulmonary sequestration case reported in the city of Huacho, Perú.